How Is the Trade-off between Adverse Selection and Discrimination Risk Affected by Genetic Testing? Theory and Experiment - David Bardey; Philippe De Donder; César Mantilla (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2017)
We develop a theoretical analysis of two widely used regulations of genetic tests, Disclosure Duty and Consent Law, and we run an experiment in order to shed light on both the take-up rate of genetic testing and on the comparison of policyholders' welfare under the two regulations. Disclosure duty forces individuals to reveal their test results to insurers, exposing them to a discrimination risk. Consent law allows them to hide any detrimental information, resulting in adverse selection. The experiment results in much lower genetic tests take-up rates with Disclosure Duty than with Consent Law, showing that subjects are very sensitive to the discrimination risk. Under Consent Law, take-up rates increase with the adverse selection intensity. We then study how individual preferences for one regulation vary as testing costs decrease. The answer depends crucially on whether the adverse selection intensity remains fixed (as in the short run) or is allowed to vary endogenously with the testing costs (as in the long run). In the short run, more people prefer Consent Law to Disclosure Duty as the testing costs decrease. In the long run, support for Consent Law may decrease when testing costs decrease, because the insurance contracts o↵ered under Consent Law become more expensive due to an increase in adverse selection.
Keywords: C91; D82; I18; 330; Consent Law; Disclosure Duty; Personalized Medicine; Test take-up rate; pooling health insurance contracts